Neo-Victorian lesbians on screen / Sarah E. Maier, Rachel M. Friars. - Maier, Sarah E. (Sarah Elizabeth), 1968-; Friars, Rachel M. (Anthem Press, 2025)
'Neo-Victorian Lesbians on Screen' argues that the on-screen portrayal of lesbians situated in the long 19th century across various countries is at the very least a dual task; the imperative project of revoicing lesbian silence and female companionship is complicated by the lack of and/or complex representation of such women in the past.